Effects of withdrawing high-fiber ingredients prior to market on growth performance, carcass characteristics, and economics in commercial finishing pigs - Coble, Kyle F.; DeRouchey, Joel M.; Dritz, Steven S.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 1,089 mixed-sex pigs (PIC 337 × 1050; initial BW 98.2 lb) were used in a 96-d study. The two diet types fed during the study were a corn-soybean meal control diet with low NDF (9.3%) and a high-fiber diet with high NDF (19%) that contained 30% dried distillers grains with solubles (DDGS) and 19% wheat middlings (midds). Pens of pigs were randomly allotted to 1 of 6 dietary feeding strategies with 25 to 27 pigs per pen and 7 replications per treatment. The six dietary strategies consisted of the corn-soybean meal control diet or high-fiber diet fed for the duration of the study, or the high-fiber diet fed until 24, 19, 14, or 9 d prior to harvest, at which time the pigs were switched to the corn-soybean meal control diet for the remainder of the study. Overall (d 0 to 96), pigs fed the high-fiber diet through the entire study compared with the corn-soy control diet had lower (P < 0.01) ADG and poorer F/G. This reduction in growth performance led to a trend for poorer (P < 0.10) caloric efficiency and lower (P < 0.01) final BW in pigs fed the high-fiber diet throughout compared to the control. For pigs fed the high-fiber diet then switched to the corn-soy control, ADG and ADFI were not different between withdrawal days, but F/G tended (linear; P < 0.07) to improve as withdrawal days increased from 0 to 24 d. Pigs fed the high-fiber diet throughout had a 9.5-lb lighter (P < 0.01) HCW compared to those fed the corn-soy control. Neither percentage yield using the farm live weight or plant live weight were significantly influenced by withdrawal days from the high-fiber diet; however, HCW increased linearly (P < 0.05) as withdrawal days increased. Backfat and loin depth both decreased (P < 0.02) in pigs fed the high-fiber diet throughout compared with those fed the corn–soybean meal diet. Loin depth increased, then decreased (quadratic; P < 0.04) as high-fiber diet withdrawal time increased. Total feed cost per pig and feed cost per lb of gain was lower (P < 0.01) for pigs fed the high-fiber diet until harvest, but carcass gain value per pig also decreased (P < 0.01) by $7.34. Total feed cost tended (P < 0.10) to increase and carcass gain value increased (P < 0.05) as high-fiber diet withdrawal time increased. Although no significant differences were observed in income over feed cost (IOFC) between treatments, switching pigs from the high-fiber diet to the corn-soybean meal diet at 14 to 19 d before market numerically increased IOFC by $1.42 to $2.30/pig over pigs fed the high-fiber diet continuously and $2.04 to 2.92/pig over pigs fed the corn-soybean meal diet throughout. These data indicate that much of the benefit in lower feed cost from feeding high-fiber diets can be captured while minimizing the reduction in revenue by switching pigs to a low-fiber, high-energy diet for 14 to 19 d prior to market.
Keywords: Finishing pig; Fiber withdrawal; Growth performance